THE CONCEPT OF THE FOOD REGIME AND TRENDS IN THE DEVELOPMENT OF THE FOOD SITUATION IN THE MODERN WORLD. Концепция Продовольственного Режима И Тенденции Развития Продовольственной Ситуации В Современном Мире - Malov, Alexander Vadimovich (2018)
This article is devoted to the study of the food regime, a concept little known in Russian academic literature. The author identifies the "theoretical and methodological platform" of the concept using a comparative approach and retrospective analysis. The ensemble of a comparative-historical approach, a method of analyzing secondary data and a forecasting method contributed to the consolidation of the concept of the food regime as a tool capable of streamlining the global stages of production, consumption and distribution of food in historical retrospect as well as in the foreseeable future. The author demonstrates that the consistent transformation of food regimes comes about due to the conflict between two principles, "protectionism" and "free trade," which are effectively adapted to different political and economic realities. The identified "sequence" is consistent with the general position of the theory of Karl Polanyi (the Double Movement) and allows us to assert that the foundation of the Fourth Food Regime will be based on a modified version of protectionism. This is confirmed by the growing popularity of the transnational movement La Via Campesina and the growing demand for its revolutionary strategy of Food Sovereignty. (English)
Keywords: double movement; food regime; food security; food sovereignty; globalization; глобализация; двойное движение; продовольственная безо-пасность; продовольственный режим; продовольственный суверенитет

Концепция Продовольственного Режима И Тенденции Развития Продовольственной Ситуации В Современном Мире - Малов, Александр Вадимович (Moscow University Political Science Bulletin Series 12, 2018)
Alternate Title: THE CONCEPT OF THE FOOD REGIME AND TRENDS IN THE DEVELOPMENT OF THE FOOD SITUATION IN THE MODERN WORLD. This article is devoted to the study of the food regime, a concept little known in Russian academic literature. The author identifies the "theoretical and methodological platform" of the concept using a comparative approach and retrospective analysis. The ensemble of a comparative-historical approach, a method of analyzing secondary data and a forecasting method contributed to the consolidation of the concept of the food regime as a tool capable of streamlining the global stages of production, consumption and distribution of food in historical retrospect as well as in the foreseeable future. The author demonstrates that the consistent transformation of food regimes comes about due to the conflict between two principles, "protectionism" and "free trade," which are effectively adapted to different political and economic realities. The identified "sequence" is consistent with the general position of the theory of Karl Polanyi (the Double Movement) and allows us to assert that the foundation of the Fourth Food Regime will be based on a modified version of protectionism. This is confirmed by the growing popularity of the transnational movement La Via Campesina and the growing demand for its revolutionary strategy of Food Sovereignty. (English)
Keywords: double movement; food regime; food security; food sovereignty; globalization; глобализация; двойное движение; продовольственная безо-пасность; продовольственный режим; продовольственный суверенитет

A Critique of Economic Determinism: Karl Polanyi's Methodology. (In Russian.) - Nureev, R. M. (Zhournal Novoi Ekonomicheskoi Associacii/Journal of the New Economic Association, 2013)
Keywords: economic determinism

ТРАДИЦИОННАЯ РЫНОЧНАЯ ЭКОНОМИКА И ЕЁ АНТИЦИКЛИЧЕСКИЙ ПОТЕНЦИАЛ В ОЦЕНКАХ ИССЛЕДОВАТЕЛЕЙ XIX-XX ВЕКОВ - Анатольевич, Орлянский Евгений (Наука о человеке: гуманитарные исследования, 2021)
The article deals with the first stage of the market economic system - the traditional market economy. The traditional market economy is considered in the assessment of its main researchers. The main goal of the study is to identify the main characteristics and features of the traditional economy, which would explain the absence of pronounced cyclical elements in it. It is assumed that several essential elements of such an economy carry the strongest countercyclical potential. The article uses the methodology of comparative analysis, which will help to find common ground among the most famous researchers of the traditional market economy. The study of the traditional market economic system was carried out in the context of overcoming the stereotype of the closed development of economic processes and the impossibility of influencing them by non-economic factors. This is confirmed by the fact that most of the countercyclical elements of the traditional market economy are derived from the spiritual and ethical sphere. At the same time, an integral part of the article is the position that this economic system retains all the characteristic features of a market economy. The traditional market economy practically did not experience cyclical tendencies in its development. This was due to the fact that this economic system contained built-in elements that ensured the absence in the traditional economy of both cyclicality itself and periodic cyclical crises.